A confocal three-dimensional micro X-ray scattering technology based on Rayleigh to Compton ratio for identifying materials with similar density and different weight percentages of low-Z elements. (July 2015) - Li, Fangzuo; Liu, Zhiguo; Sun, Tianxi; Yang, Chaolin; Sun, Xuepeng; Sun, Weiyuan; He, Jialin; Ding, Xunliang
Abstract: A point-by-point Rayleigh to Compton scattering ratio (R/C) imaging for two polymer materials with similar density and different weight percentages of low-Z elements was carried out by using the confocal three-dimensional (3D) micro X-ray scatter tomographic technology based on polycapillary X-ray optics. This confocal 3D micro X-ray scatter tomographic technique was based on the confocal configuration of a polycapillary focusing X-ray lens (PFXRL) in the excitation channel and a polycapillary parallel X-ray lens (PPXRL) in the detection channel, which let only the X-rays scattered from the confocal micro-volume overlapped by the input focal spot of the PPXRL and the output focal spot of the PFXRL be detected by the detector. The main scope of this study was using the confocal 3D micro X-ray scattering tomography based on the R/C ratio to characterize and identify materials with nearly equal low density and different weight percentages of low-Z elements, as other radiological techniques are difficult to discriminate them for their very close attenuation coefficients μ . A mapping of R/C ratios for two thermoplastic polymer materials was obtained, which provided the spatially resolved distribution of their effective atom numbers, and their differences were accordingly presented. This confocal 3D micro X-ray scatter tomographic technique has potential applications in fields such as material identification, dosimetry, medical imaging, carbonation cancer, and so on. Highlights: Confocal technology based on Rayleigh to Compton scattering ratio is presented. We obtained a map of effective atom numbers of two polymer samples. Confocal technology has potential applications in material identifications.